Design of a quick couping fixture for fuel cell performance evaluation - Low, Ee Ter. (2011)
Polymer electrolyte membrane fuel cell (PEMFC) is an emergent technology that promises clean and efficient transportation of energy. Researchers are currently developing and evaluating different types of membranes as well as flow field designs that will unravel the full potential of this technology.